Shoot for the moon : the space race and the extraordinary voyage of Apollo 11 - Donovan, Jim, 1954- (Little, Brown and Company, 2019)
ON JULY 20, 1969, Neil Armstrong and Buzz Aldrin became the first humans to walk on the moon. One of the world's greatest technological achievements-and a triumph of American spirit and ingenuity-the Apollo 11 mission was a mammoth undertaking involving more than 410,000 men and women dedicated to winning the space race against the Soviets. Set amid the tensions of the Cold War and the upheavals of the sixties, and filled with first-person, behind-the-scenes details, Shoot for the Moon is a gripping account of the dangers, the challenges, and the sheer determination that defined not only Apollo 11, but also the Mercury and Gemini missions that came before it. From the shock of Sputnik and the heart-stopping final minutes of John Glenn's Mercury flight to the deadly whirligig of Gemini 8, the doomed Apollo 1 mission, and that perilous landing on the Sea of Tranquility-when the entire world held its breath while Armstrong and Aldrin battled computer alarms, low fuel, and other problems- James Donovan tells the whole story.